Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision - Salmela, Jukka; Härmä, Oskari; Taylor, Derek J. (Zootaxa, 2021)
Chaoborus flavicans (Meigen) is a widespread and much studied lacustrine phantom midge. As larvae, these insects are important aquatic predators. Based on the available type material, morphology of immature stages and adults, their aquatic habitat, and DNA barcodes, C. flavicans is shown to be a composite of at least four species, with three of these named here. Chaoborus flavicans is primarily a lake-dwelling species with a Holarctic range. Chaoborus albipes (Johannsen, 1903 stat. rev.) and C. posio Salmela sp. n. are pond-dwelling Holarctic and north European species, respectively. The position of the larval subordinate mandibular tooth at the vertex of the second and fourth teeth is a synapomorphy of the Chaoborus flavicans species complex. We present an identification key to fourth instar larvae, pupae, and adult males. We also designate the lectotype and paralectotypes of Sayomyia rotundifolia Felt, 1904 (syn. nov. of C. albipes). We hypothesize that a fourth species of the species complex is present in Japan. Our revision indicates that Holarctic shallow ponds contain a hidden diversity of predators (C. albipes and C. posio sp. n.).